Escape to Papua New Guinea [videorecording (DVD)] - Spacek, Libor; Dolezalova, Petra (Galloping Films, 2024)
Papua New Guinea is the most mysterious and anthropologically diverse island/country in the world that hosts one of the widest diversities of marine life.